(untitled) (Revista da Faculdade de Odontologia - UPF, 2016)
Objective: The present study aimed to determine the occlusal characteristics and prevalence of malocclusion among Brazilianpreschool children. Subjects and method: A cross-sectional study was conducted with 1004 children aged 2-5 years enrolled in public preschools of the city of Canoas, RS, Brazil. A questionnaire was administered to guardians addressing demographic, socioeconomic, and behavioral characteristics of the children and their families. The clinical exam was performed by previously calibrated dentists and the characteristics of the primary dentition were verified according to set criteria. Data analysis was performed through the chi-square test. Results: Stability in the sagittal and transverse planes of the posterior region, and a variability of incisal relations in the primary dentition were verified. The findings show high prevalence of malocclusion (70.3%) and its association with age. Conclusion: Considering the high prevalence of malocclusion in primary dentition, implementing educational programs and prevention measures for preschool children is highlighted.